The Role of the Qur’an as a Source of Inspiration in the Development of Science and Technology - Rouf, M. Abd.; Ananda Emiel Kamala; Fuad Ngainul Yaqin (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract This study aims to examine and explain the role of the Qur’an as a source of inspiration, a conceptual reference, and an ethical foundation in the development of science and technology, and to assess its relevance to the objectives of national education in shaping individuals who are faithful and pious. Through theme identification, narrative synthesis, and descriptive interpretation, this study reveals the role of the Qur’an as a driver of empirical observation, a basis for scientific ethics, and a source of theoretical insight for modern research. This study employs a descriptive qualitative method with a narrative literature review approach to analyze ten scholarly articles on “The Qur’an and Science/Technology.” The findings indicate that the Qur’an encourages scientific and technological development by promoting observation of nature, fostering ethical principles in knowledge, and describing natural phenomena. In conclusion, the Qur’an catalyzes innovation aligned with human values. Keywords: Human Values; Qur’an; Science.   Abstrak Penelitian ini bertujuan untuk mengkaji dan menjelaskan peran Al-Qur'an sebagai sumber inspirasi, rujukan konseptual, dan landasan etis dalam pengembangan sains dan teknologi, serta relevansinya dengan tujuan pendidikan nasional dalam membentuk manusia yang beriman dan bertakwa. Melalui identifikasi tema, sintesis naratif, dan interpretasi deskriptif, penelitian ini mengungkap peran Al-Qur'an sebagai pendorong observasi empiris, landasan etika ilmiah, dan wawasan teoritis untuk penelitian modern. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan narative literature review untuk menganalisis 10 artikel ilmiah tentang "Al-Qur'an dan Sains/Teknologi". Temuan menunjukkan bahwa Al-Qur'an memotivasi pengembangan ilmiah dan teknologi dengan mendukung observasi alam, etika pengetahuan, serta menggambarkan fenomena alam. Kesimpulannya, Al-Qur'an berfungsi sebagai katalisator bagi inovasi yang sejalan dengan nilai-nilai kemanusiaan. Kata Kunci: Al-Quran; Nilai Kemanusiaan; Sains.